Validity and measurement invariance of abbreviated scales of the State-Trait Anxiety Inventory (STAI-Y) in a population of Italian young adults - Giuseppe Valente; Pierluigi Diotaiuti; Stefano Corrado; Beatrice Tosti; Alessandra Zanon; Stefania Mancone (Frontiers in Psychology)
IntroductionThis study evaluates the validity and measurement invariance of the 8-item scales of the State-Trait Anxiety Inventory (STAI) across gender and age. Originally developed by Spielberger (STAI-Y), these scales have been shortened to create more efficient versions without compromising psychometric robustness.MethodsA sample of Italian young adults, aged between 18 and 36 years, completed the abbreviated scales. The scales were assessed for internal consistency, convergent validity with the Endler Multidimensional Anxiety Scales (EMAS), and measurement invariance across gender and age.ResultsThe results demonstrated excellent internal consistency and significant correlations with the EMAS, supporting the convergent validity of the STAI-S-8 and STAI-T-8. Both scales retained balanced factorial structures and robust anxiety measurement capabilities. Measurement invariance was confirmed across gender and age, indicating the scales' reliability for anxiety assessment in young adults regardless of demographic differences.DiscussionWhile the findings underscore the practical utility of the 8-item STAI scales for rapid anxiety assessment in clinical and research settings, limitations include the absence of a clinical sample and reliance on self-report measures, which may introduce biases. Future research should include clinical populations and explore cultural differences in anxiety manifestation. Despite these limitations, the 8-item STAI scales offer valid, reliable, and efficient tools for measuring anxiety, with significant implications for timely interventions and enhanced psychological assessment.